Re-Fracture as Impact of Rigid Implant and Bone Osteoporosis: A Case Report - Huda Fajar Arianto; Yunus Basrewan (Universitas Airlangga, 2022)
Background: The increasing life expectancy of the world population associated with osteopenia and osteoporosis leads to low-energy fractures, especially in the lower limb. The overture of locking plates has widened the area of close fracture fixation, and it is essential to justify and optimize their usage. This study aims to report the potential postoperative re-fracture after implant removal and as a consequence of bone osteoporosis.Case report: We present a re-fracture of proximal femur case in 60 years old female after a trivial fall into her right femur. This patient underwent a removal implant surgery a week before in the same spot where she fell. The open surgery was made with the same incision, and we do the Open Reduction Internal Fixation for her. Discussion: The major design of the fixation tool is to secure the fracture with less effect on native axial load stress from the whole bone. Stress shielding caused due to firm bone-implant results in its resorption. The bone degradation underneath gives rise to the plate's collapse, resulting in repeated bone breakage. Early discharge, continued weight-bearing training for proximal femur fractures were associated with speedy improvement in daily activities. The photodynamic polymer liquid was the latest technology for bone stabilization.Conclusion: Rigid bone plates can cause stress shielding, and when the implants are removed, re-fracture easily happens. Therefore, discharge of patients quickly for weight-bearing training in proximal femur fractures was encouraged to promote better healing.